Primary Cardiac Hodgkin Lymphoma – Case Report - prodanovic, boris r; prodanović, boris r (Scripta Medica, 2019)
Primary cardiac tumors are rare, with an incidence of 0,056%. The most of primary cardiac tumors are benign tumors, only 10% are malignant, and 1% from malignant tumors are primary cardiac lymphoma (PCL). From the clinical standpoint, PCL is a non-Hodgkin lymphoma presenting as cardiac disease in rightsided chambers in elderly population. It has been presented young men with Hodgkin PCL, that has been successfully treated with transplantation of the hematopoietic stem cells, leading to stable remission of the disease that has been maintained for 12 years. Key words: primary cardiac lymphoma, Hodgkin lymphoma, transplantation of the hematopoetic stem cell